‘Blood’ Kinship and Kinship in Christ’s Blood: Nomadic Evangelism in the Nenets Tundra - Tatiana Vagramenko (Journal of Ethnology and Folkloristics)
The article addresses a conflicting encounter of two ideologies of kinship, ‘natural’ and ‘religious’, among the newly established Evangelical communities of Nenets in the Polar Ural and Yamal tundra. An ideology of Christian kinship, as an outcome of ‘spiritual re-birth’, was introduced through Nenets religious conversion. The article argues that although the born-again experience often turned against ancestral traditions and Nenets traditional kinship ties, the Nenets kinship system became a platform upon which the conversion mechanism was furthered and determined in the Nenets tundra.